Gray Code ADC Based on an Analog Neural Circuit - Daponte, P.; Grimaldi, D.; Michaeli, L. (Radioengineering Society, 1995)
In this paper a new neural ADC design is presented, which is based on the idea to replace all functional components needed in the ADC block scheme by a simple connection of neurons. Transformation of ADC functional scheme into an analog neural structure and its computer simulation is one of the main results of this paper. Furthermore, a discrete component prototype of the proposed A/D converter is discussed and experimental results are also given.
Keywords: AD converter; gray code; neural networks